THE RELATIONSHIP OF ORGANIZATIONAL COMMUNICATION FOR IMPROVE EMPLOYEE ACHIEVEMENT IN THE OF EDUCATIONAL INSTITUTIONS - Musliamin Musliamin (Institut Agama Islam Negeri Bone, 2022)
This study discusses the relationship between organizational communication and employee performance improvement in the of educational institutions. The purpose of this study was to find out the general description of the concept of communication relations in an organization in the process of increasing employee performance in an educational institution. This study use a literature review design, which is a research method used to systematically and explicitly synthesize a concept from previous research articles. The source of data in this research is by searching articles in several databases such as Garuda, EBSCO, IISTE, Social Sciences and Google Scholar. The results of the study show that there is a positive relationship between organizational communication and performance indicating that if communication between the leaders of an organizational institution is positive there will be an increase in employee performance, organizational communication refers to a series of processes that imply the transmission of messages between members of an institution that allows interaction between them. Communication complexity refers to the performance of various employees at different hierarchical levels, as well as different job performance functions.Keywords: Organizational Communication; Employee Performance; Educational Institutions